(In)Security Regime among African Youth: The Age and Law Curfew (Glocalism: Journal of Culture, Politics and Innovation, 2015)
this paper purports to present the account of twin phenomena of age and constitution that anointed the relegation of African youth to the wastebasket of oppression. African youth have been studied by various scholars; and social, economic, and political statistical analyses of the youth were habitually deduced from [un]employment quotient. According to National Treasury discussion paper[1] this instrument may not be a reliable tool in either understanding insecurity regimes threatening the youth in Africa and may not suffice in championing policy course for a secured African youth. [Un]employment are only symptoms of asymmetrical laws governing many African states. The principal problems are the constitution, and age limitations respectively (Ombagi 2012). In this guide, the instrument valid for testing and indeed, observing the true condition of young Africans are: the roles of state’s constitution; and the Age Grade limitation factors. These, are critical in the development and security of the youth. George McGovern cited in Jeanette Rankin (2012) noted that he [was] fed up to the ears with old men dreaming up wars for young people to die. Two salient factors, rudimentary to youth insecurity in the region in McGovern’s assertions are the law which authorises war and the age grade legally targeted in the war. In assortment of ways, constitutions provide the basis for definition, qualification and categorisation of the youth, who in turn are the direct sufferers of numerous human and state insecurity conditions forced on them by law. Constitution, therefore, plays exclusivist roles and enables the central authority to enforce rules on, and dictate norms for the youth. Despite the need for the state to adjust its behavior to reflect the actual or anticipated preferences of all citizens through a process of policy coordination, laws deprive the youth.
Keywords: Africa; constitution; education; security; youth